Tourism Sector Employment Elasticity in Nepal: An Analysis - Thapa-Parajuli, Resham; Paudel, Ramesh C. (Economic Journal of Nepal, 2018)
Given Nepal's location and geographical situation, the country has unique comparative advantages in the tourism sector. The Nepalese tourism sector largely remains labour intensive due to insufficient investment in quality infrastructure and technology. Even in this background, the tourism sector contributes a significant share of GDP and employment in Nepal. Knowing the employment elasticities to various tourism indicators helps to understand the tourism sector and make sound policy inferences. For this purpose, the paper combined the annual data from the WorldTravel and Tourism Council (WTTC) on direct and indirect contribution to employment and GDP with the total tourist arrival and the average length of stay data from Nepal Tourism Statistics to estimate a simple double log-linear equation-based individual elasticity coefficients. The findings of this paper suggest that besides government personal travel and tourism spending, other all elasticities are positive. Among them, the average length of stay has the most substantial and positive employment elasticity coefficient, which is relatively higher than the total number of arrival elasticity too. Thus, it is better to target to extend the length of stay than the arrival of tourist, other things remaining the same